Winegrape similarities and concentrations: implications - German Puga; Kym Anderson (IVES Technical Reviews)
In a previous article in this journal, we described the mixes of winegrape varieties across countries in terms of both similarities and concentrations. We showed that countries are becoming more similar in their mixes of winegrape varieties between them and with respect to the world as a whole, and that they are becoming more concentrated. The aim of this article is to discuss the implications of these recent changes in similarities and concentrations. These insights are based on those of a recent scientific journal article (Puga and Anderson 2023), as well as those from other work – part of which is first published here.